Sistem Konversi Energi Panas Briket Arang Menjadi Energi Listrik Sebagai Alat Charger Baterai Menggunakan Termoelektrik - Andi, La Ode; Balaka, Ridway; Mangalla, Lukas Kano (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2023)
Regarding the conversion system with a thermoelectric element which allows it to be used anytime and anywhere, that's why you need to position the tool correctly. With that, the research aims to find out the voltage produced and the performance of thermoelectrics as a generator of electrical energy. The method used in this research is a system for converting briquette heat energy into electrical energy. The variations in the research experiment are fan cooling 1, fan cooling 2 and water cooling. By using a charcoal briquette heater and three variations of cooling, the average voltage of cooling fan 1 0.660 V, cooling fan 2 0.769 V, water cooling 0.903 V can be produced and the average current of cooling fan 1 is 0.029 A, cooling fan 2 is 0.034 A, cooling Water 0.039 A. The characteristics of the resulting temperature difference show a significant increase along with the length of combustion time. The resulting voltage is higher if the hot combustion of the briquettes is carried out with a variation of water cooling. Keywords: Briquettes, electricity, hot side, thermoelectric, and voltage